Identification and Frequency of Candida Patient Isolates by CHROMagar Candida Method - Seyyed Hasan Mirhendi; Kouichi Makimura; Mohammad Reza Shidfar; Leila Hossienpour (پزشکی بالینی ابن سینا, 2007)
Introduction & Objective: Candida species can cause opportunistic infections in human. Although Candida albicans is major pathogenic species, non-albicans species of Candida such as C. glabrata , C. tropicalis and C. krusei have been increasingly reported. Identification of Candida species is essential for effective antifungal therapy and for infection control purposes. In the present study the commercial medium CHROMagar Candida was used as a differential method for identification of the yeasts isolated from patients.